Clinical and epidemiological characteristics of male hypogonadism in type 2 diabetes in Russia: combined analysis of study data for the period 2005–2022 - M. O. Chernova; D. I. Esaulenko; E. R. Rozhivanova; R. V. Rozhivanov; G. A. Mel’nichenko; M. V. Shestakova; N. G. Mokrysheva (Сахарный диабет)
Background: Male hypogonadism is associated with type 2 diabetes mellitus (T2DM), therefore, it is of interest to study its clinical and epidemiological characteristics. These data are published, but their fragmentation and small sample sizes are a problem. A summary assessment of the combined primary data of the conducted studies will provide sufficient representativeness and will allow to extrapolate the results to the general Russian population with T2DM.Aim: Assessment of the clinical and epidemiological characteristics and aggravating factors of male hypogonadism in T2DM in Russia.Materials and methods: A Combining primary data (anamnesis, anthropometric indicators, laboratory tests) of full-design, cross-sectional, screening studies of hypogonadism in men with T2DM conducted on the territory of the Russian Federation in the period from 2005 to 2022. The groups were compared using the Mann-Whitney U-test for quantitative indicators and χ² with Yates’ correction for qualitative ones. Differences were considered statistically significant with p <0,05. The groups were compared using the Mann-Whitney U-test and χ² with Yates correction. Differences were considered statistically significant at p<0.05.Results: Hypogonadism was detected in 893 of 1576 men (56,7%) with T2DM. Patients with hypogonadism were statistically significantly older, had higher body mass index (BMI), worse glycemic control than eugonadal men. There was statistically significantly higher prevalence of macroangiopathies and polyneuropathy in hypogonadal patients.Conclusion: The prevalence of male hypogonadism in T2DM 56,7%. Its development is due to age, obesity, worse glycemic control. Hypogonadism syndrome is associated with the development of diabetic macroangiopathy and polyneuropathy. Severe violation of glycemic control (glycated hemoglobin (HbA1c) 10% or more) significantly reduces testosterone production and increases the prevalence of hypogonadism.